2019
DOI: 10.3390/app9194121
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis and Technology Evaluation for a Roadable Personal Air Vehicle at the Conceptual Design Stage

Abstract: In this study, the technology identification, evaluation, and selection (TIES) method was implemented to explore an optimum design space appropriate for a personal air vehicle (PAV) at the conceptual design stage. A morphological matrix was employed to identify possible alternative configurations and performance targets. The Microsoft Excel add-in JMP, a commercial statistical tool, and a PAV sizing tool developed for this study were used for modelling and simulation. After the screening test, seven design var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, data of the power to weight in other papers were hp/kg so that we converted the unit using the following equation. The maximum take-off weight is one of the factors influencing not only the aircraft performance but also the cost analysis performed using weight data [12]. In this study, 200 kg, the average maximum take-off weight of conventional solar aircraft as shown in Table 7, was used as an initial assumption value.…”
Section: Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, data of the power to weight in other papers were hp/kg so that we converted the unit using the following equation. The maximum take-off weight is one of the factors influencing not only the aircraft performance but also the cost analysis performed using weight data [12]. In this study, 200 kg, the average maximum take-off weight of conventional solar aircraft as shown in Table 7, was used as an initial assumption value.…”
Section: Problem Definitionmentioning
confidence: 99%
“…The main independent design variables necessary for calculating this required power and available power for a solar aircraft are shown in Table 8. As many independent design variables change flexibly in the conceptual design stage as well, calculation should be repeated many times in a specific range in order to find the optimal design conditions [12]. Table 8 shows the major independent design variables and specific ranges of the minimum and maximum values of each variable.…”
Section: Baseline and Alternative Concepts Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of the aircraft parameters, the sensitivity analysis method [23] and correlation analysis method were widely used to dig out important parameters whose influence was most obvious [24,25]. The orthogonal test and some novel methods, such as the technology identification, evaluation and selection method in [26] and hybrid algorithm in [27], were employed to explore an optimal design space and parameter estimation in aircraft parameters analysis as well.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is not enough data, manufacturers are having difficulty in designing and experimenting with various designs of eVTOL PAVs. To efficiently design an eVTOL PAV, it is necessary to employ various optimization techniques from the conceptual design stage [9].…”
Section: Introductionmentioning
confidence: 99%